2014
DOI: 10.1097/ncc.0b013e31827ca807
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Male Spouses of Women With Breast Cancer

Abstract: The findings underscore the importance of assessing for and fostering hope and self-efficacy as well as decreasing guilt in male spouses of women with breast cancer to improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
4
30
1
2
Order By: Relevance
“…Our study focuses on spouses because they are often the first to provide caregiving (Duggleby et al, 2014;Pinquart, & S€ orensen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our study focuses on spouses because they are often the first to provide caregiving (Duggleby et al, 2014;Pinquart, & S€ orensen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While earlier works only postulated increased difficulties for younger partners (Baucom et al, 2005), the results of the present study contribute to the evidence collected by the few studies to date that found a more detrimental effect of the patient diagnosis on the quality of life of younger partners, who are faced especially with concerns about everyday life, negative affectivity, apprehension about the future and the couple cohesion (Antoine et al, 2012;Christophe et al, 2015;Duggleby et al,2014;Hasson-Ohayon et al, 2014;Vanlemmens et al, 2015a;. Finally, the higher score on illness intrusiveness is a finding that is similar to results emerged in the literature about cancer caregiving, which has identified higher burden, mood disturbances and worse quality of life for those who assume this role at a 37 General population and cancer patient norms for the Functional Assessment of Cancer Therapy -General (FACT-G; Cella, 2004) have been collected for Physical, Social/Family, Emotional and Functional Wellbeing and the FACT General score.…”
Section: Discussionsupporting
confidence: 64%
“…Numerous authors affirm that male partners of younger women can be overwhelmed with multiple and competing caregiving demands, higher depressive symptoms, and worse quality of life (Antoine et al, 2012;Baucom et al, 2005;Duggleby, Doell, Cooper, Thomas, & Ghosh, 2014;Hasson-Ohayon, Goldzweig, Dorfman, & Uziely, 2014). Only three studies were identified to include both younger breast cancer patients and their partners (Antoine et al, 2012;Vanlemmens et al, 2012b).…”
Section: Impact Of Breast Cancer On the Couple Relationship Of Youngementioning
confidence: 99%
“…Bereavement is known to cause a significant impact on an individual and even modify the life. Whyte et al [12] and Dietz et al [13] studied the impact of the death of parents; while Duggleby et al [14] and Yopp and Rosenstein[15] studied the impact of the death of a spouse. Rostila et al [16] investigated the effect of sibbling's demise while Yeates et al [17] studied the effect of children's death on parents, and Creighton et al [18] showed that people are more profoundly affected by the death of friends than that of other relatives.…”
Section: Introductionmentioning
confidence: 99%